Fibroblast Heterogeneity in and Its Implications for Plastic and Reconstructive Surgery: A Basic Science Review. Issue 6 (June 2020) - desJardins-Park, Heather E.; Chinta, Malini S.; Foster, Deshka S.; Borrelli, Mimi R.; Shen, Abra H.; Wan, Derrick C.; Longaker, Michael T.
Abstract : Summary: Fibroblasts' integral role in tissue development, maintenance, and disease represents a fast-growing field of basic science research. Although fibroblasts were long thought to be a homogeneous cell population, recent research has illuminated the unforeseen complexity of these cells, giving rise to the rapidly expanding research field of "fibroblast heterogeneity." Fibroblasts play a critical role in states of tissue fibrosis such as skin scarring, which affects hundreds of millions of patients annually and causes severe aesthetic, developmental, and functional morbidity. Beyond scarring, major organ fibrosis is an enormous public health concern responsible for nearly half of all deaths in the United States. Because fibrosis is a conserved response to tissue damage in all organs, the study of fibroblasts throughout the body may help us to understand their role in the conditions most relevant to plastic and reconstructive surgery—for instance, skin scarring (eg, from burns, traumatic lacerations, or surgical incisions), "pathological" scarring (hypertrophic scars, keloids), and capsular contracture. Here, we present a basic science review of fibroblast heterogeneity in wound healing, cancer, organ fibrosis, and human dermal architecture. The field of fibroblast heterogeneity is young, and many of the insights discussed have yet to be translated clinically. However, plastic surgeons stand in a unique position to bridge these discoveries into clinical realities. We hope this information can spur readers to consider both what questions in plastic surgery can be studied from the lens of fibroblast heterogeneity, and how these preclinical insights can be translated to improving care of our patients.